2019
DOI: 10.1380/ejssnt.2019.163
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Diffraction, XPS, and Raman Spectroscopy of Coated ZnO:Al (1—7 at%) Nanoparticles

Abstract: Group III elements doping for zinc oxide is currently attracting much attention for the study of absorber layer in nano-optoelectronic and photovoltaic devices as an alternative route to indium tin oxide (ITO) due to their optimized properties. In this report, Al-doped ZnO (AZO, Al: 1−7 at%) nanoparticles have been successfully deposited onto glass substrates using sol-gel process, and investigated by techniques such as X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The Zn2p high-resolution spectrum shows that in the TiO 2 /ZnO hybrid nanosponges the doublet peaks corresponding to Zn2p 1/2 and Zn2p 3/2 can be appreciated at approximately 1045.2 and 1022 eV, respectively, and the distance between them is about 23.2 eV. These results proved that Zn species are in its Zn +2 oxidation state, confirming the presence of ZnO in the TiO 2 /ZnO nanostructures [ 23 , 25 , 49 , 51 , 52 , 54 ].…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The Zn2p high-resolution spectrum shows that in the TiO 2 /ZnO hybrid nanosponges the doublet peaks corresponding to Zn2p 1/2 and Zn2p 3/2 can be appreciated at approximately 1045.2 and 1022 eV, respectively, and the distance between them is about 23.2 eV. These results proved that Zn species are in its Zn +2 oxidation state, confirming the presence of ZnO in the TiO 2 /ZnO nanostructures [ 23 , 25 , 49 , 51 , 52 , 54 ].…”
Section: Resultsmentioning
confidence: 61%
“…It can be observed that, in all XPS spectra, the peak corresponding to C1s at position 284.6 eV appears, which is a fact related to the organic species involved in the preparation (glycerol) and to the contaminants adsorbed in the nanostructures. C1s peak position can be used as a reference for the rest of the peaks involved in the XPS spectra [ 23 , 51 ]. As expected, peaks related to Zn are only observed in TiO 2 /ZnO hybrid nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy has been used for qualitative and quantitative studies of electronphonon interaction in nanostructured ZnO films in CF/ZnO_nr and CF/ZnO_ns samples because it is sensitive to lattice distortions, crystal defects, and phase transformations [13,[15][16][17][18][19][20]. The vibrational phonon modes of the nanostructured ZnO layers were characterized using a Raman microscope (Thermofisher Nicolet DXR Microscope, Thermo Fisher Scientific Inc., Waltham, MA, USA) with a solid-state diode green laser with an excitation wavelength of 532 nm and a power of 10 mW.…”
Section: Methodsmentioning
confidence: 99%
“…The average crystallite size (D) was determined from the broadening of X-ray lines using the Scherrer formula [57]:…”
Section: Optical Spectra and Surface Resistancementioning
confidence: 99%